FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA (STUDI PADA MASA PANDEMI COVID-19) - Febryanti Simon (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Inflation is one of the indicators in measuring the economic stability in a country. The purpose of this study is to determine and analyzed the impact of pandemic time of covid-19 to inflation in Indonesia. In this research, there are three factors that can effect to inflation; exchange rate, BI rate and money circulation. Data that used in this research in secondary data that collected from www.bi.go.id and www.bps.go.id. Based on the result, it is concluded that BI rate has a significant effect on the inflation. Then, the other variables; exchange rate dan money circulation has no significant effect to inflation.